Awareness of Cancer among Adults in a Rural Health Field Practice Area: A Cross-Sectional Study from a Tertiary Medical College - Sudhakar.S; Pradeep.T.S (Disease and Health: Research Developments Vol. 1, 2024)
Background: India has many factors such as an aging population with poor awareness, increased disparity due to varied economic conditions, and environmental influences leading to higher incidence and mortality rates of cancer. The present study was planned with the objective of assessing the awareness of cancer among villagers and the factors associated with awareness of cancer. Materials and Methods: The present study was a cross-sectional study carried out for a period of 1 year in 20 villages of Devarayasamudra where cancer awareness was assessed using a pretested questionnaire. The sample size was calculated based on a pilot study. Individuals above 18 years were included in the study and participants who were already diagnosed from cancer or family members suffering from cancer were excluded from the study. Data was entered in an Excel sheet and analysed using SPSS V 22. Descriptive statistics were applied, and to assess differences, t-tests and ANOVA were used. A p-value of less than 0.05 was considered statistically significant. Results: Out of 425 villagers who took part in the study, 66.4% belonged to the nuclear family and 31.1% belonged to the joint family as per BG Prasad Classification 2024. Comparing the awareness scores among the villagers, those who were aged 61 years and above, those belonging to joint family, Class I Bramha Govind Prasad classification 2024 and graduates had higher awareness scores with statistically significant p-value. Conclusion: The present study provides evidence that awareness regarding cancer is poor among villagers and there is an immediate need for strengthening awareness initiatives regarding causation of cancers, risk factors of cancer, early detection and prevention. Only Information education and communication (IEC) activities close the gaps between the providers and beneficiary which in turn, leads to decreased mortality and drastic improvement in survival rates even at advanced stages of cancer. The present study recommends adding more cancer awareness sessions to be held at primary health centers, Anganwadi centers and health wellness centers where villagers access their health care.